2021
DOI: 10.1016/j.vph.2021.106882
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism in COVID-19 compared to non-COVID-19 cohorts: A systematic review with meta-analysis

Abstract: Background Many studies confirmed an association between COVID-19 and venous thromboembolism (VTE). Whether the risk of VTE significantly differed between COVID-19 cohorts and non-COVID-19 cohorts with similar disease severity remains unknown. Objectives The aim of this systematic review with meta-analysis was to compare the rate of VTE between COVID-19 and non-COVID-19 cohorts with similar disease severity. Methods A systematic literature se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 52 publications
1
36
2
3
Order By: Relevance
“…As strengths, this is the first study reporting the RD of venous thrombotic events between COVID-19 and non-COVID-19 patients. The meta-analysis by Mai et al [11] evaluated the risk ratio (RR), but that could not be applicable since there were no randomized, controlled studies on this specific topic, and based on this, we decided to evaluate the RD. Furthermore, comparing this meta-analysis with the paper by Mai et al [11], we included five more studies and 971,727 more patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As strengths, this is the first study reporting the RD of venous thrombotic events between COVID-19 and non-COVID-19 patients. The meta-analysis by Mai et al [11] evaluated the risk ratio (RR), but that could not be applicable since there were no randomized, controlled studies on this specific topic, and based on this, we decided to evaluate the RD. Furthermore, comparing this meta-analysis with the paper by Mai et al [11], we included five more studies and 971,727 more patients.…”
Section: Discussionmentioning
confidence: 99%
“…Precipitating factors for thrombotic complications in hospitalized COVID-19 patients include inflammation, activation of the coagulation system, hypoxia, immobilization, diffuse intravascular coagulation, and endothelial dysfunction [5][6][7][8][9][10]. A higher incidence of thrombotic complications is reported in particular in COVID-19 patients admitted to the intensive care unit (ICU) [1,11]. In patients with respiratory tract infections, including influenza A virus (H1N1), many studies have demonstrated an increased incidence of thromboembolic complications [12,13], but evidence is lacking regarding the risk difference (RD) of the occurrence of venous thromboembolism (VTE) (including pulmonary embolism (PE) and deep venous thrombosis (DVT)) between COVID-19 patients and non-COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A difference was reported after analyzing the subgroups of patients who were admitted to the intensive care unit (ICU). Critically ill patients had an increased risk of VTE in the COVID-19 cohort compared to non-COVID-19 patients admitted to the ICU (RR 3.10; 95% CI 1.54–6, 23), which was not observed in cohorts of non-ICU patients (RR 0.95; 95% CI 0.81–1.11) (P interaction = 0.001) [ 62 ].…”
Section: Pathophysiology Of Arterial and Venous Thrombosismentioning
confidence: 99%
“…Однако использование гепарина и других гликозаминогликанов в качестве противовирусной терапии обладает значительным потенциалом для будущего клинического применения. Использование гепарансульфата в качестве препятствия для проникновения вируса в клетку актуально для всех коронавирусов человека, а также для вируса гепатита С и семейства герпесвирусов [20,21]. При более глубоком понимании эта терапевтическая стратегия может быть оптимизирована для COVID-19.…”
Section: доклинические свидетельства о противовирусной активности гепарина при Covid-19unclassified